KEEFEKTIFAN PENGGUNAAN MEDIA FILM DALAM PEMBELAJARAN MENULIS TEKS CERPEN SISWA KELAS VII SMP NEGERI 34 MAKASSAR - Andi Nur Faizah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2019)
The study aims at describing the effectiveness of the use of film media in learning to write short story of class VII students at SMPN 34 Makassar. The study is an experimental true design with posttest-only control design. The study was conducted at SMPN 34 Makassar. The populations of the study were 292 students of class VII. The samples were taken by employing simple random sampling and obtained class VII1 as the experiment class and class VII3 as the control class. Data collections were then analyzed using descriptive statistic analysis an inferential statistics analysis. The results of the study indicated that students’ ability at the experiment class that wrote short story by employing film media showed extremely sufficient result. Students who were able to abtain above the set KKM was 83,3% or 25 students, and students who obtained below the set KKM was 16,7% or 5 students. On the other hand, students’ ability at the control class that wrote short story by employing conventional media (pictures) showed sufficient result. Students who were able to abtain above the set KKM was 54,8% or 17 students, and students who obtained below the set KKM was 45,2% or 14 students. So, the results indicated that the use of film media is effective to be used in learning to write short story proved by the hypothesis test which used inferential statistic of independent sample test obtained the t score by 4,405 with the independent degree 59 at the level of significant p= 0,000 because α = 0,05 > p = 0,000 so H0 hypothesis was rejected and H1 hypothesis was accepted. Suggestions based on the study are teachers should use variation, one of the examples is by using film media in learning to write short story. Students should be active to learn how to write and should have more practices in writing short story. Students should be active to learn how to write and should have more practices in writing short story. The researches should use this research as a reference to conduct further study with different learning strategy to obtain alternative of learning strategies.